Analysis The Effectiveness of E-Court System at The Religious Court of Bangil Based on Simple Principles Quickly and Low Cost - Sakinah, Nur Ainun (Indonesia Law Reform Journal, 2023)
A system can be declared successful if its application in the field has achieved predetermined objectives. The Supreme Court as the highest agency in the judicial sphere has issued a system to register cases and trials in court electronically, one of which is the Bangil Religious Court. The purpose of the study was to determine the application of the e-court system in the examination of cases at the Bangil Religious Court and to determine the effectiveness of the e-court system at the Bangil Religious Court. Research methods used by researchers are sociological empirical research methods that describe the actual environmental conditions of society supported by data and facts obtained by conducting interviews and observations. The results showed that: 1) The examination of cases at the Bangil Religious Court has not fully implemented the examination of cases using the e-court system because one of the agendas for examining cases in the trial, namely the agenda of evidence, is still carried out manually. 2) Effectiveness of e-court  system implementation The Bangil Religious Court cannot run effectively because 4 factors of legal effectiveness cannot be met, namely Law Enforcement Factors there are obstacles experienced by judges in the verification process in  the e-court system, Facilities and Infrastructure Factors related to network system constraints from the center and facilities that are less attractive to the community, Community Factors that do not understand technological developments, Cultural Factors The difficulty of transitioning people's way of life from conventional to electronic. The factor that is fulfilled is Law Enforcement Factors evidenced by the issuance of PERMA Number 1 of 2019. Suggestion that the Supreme Court improve network repair and maintenance on the e-court system to avoid system errors at certain times and often conduct socialization related to e-court renewal.